Gallbladder volvulus - Abdelrahman, Zeinab AbdelMohsen; Omar, Razana Mohd; Mirza, Salman; Turkmen, Suha (WILEY, 2022)
Gallbladder volvulus is a rare entity. The condition results in rotation of the gallbladder on its mesentery along the axis of cystic duct and artery. Gallbladder volvulus is a condition in which the organ twists on its long axis to the point where its vascular supply is compromised.
Keywords: emergency; Gallbladder; ultrasound; volvulus